The Effect of Product Quality, Service Quality, and Price on Customer Satisfaction and Loyalty at CV. Bandung Clothing Factory - Pramudia, Wizaldi; Jaelani, Evan (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of product quality, service quality, and price on customer satisfaction and loyalty at CV. Pabrik Baju Bandung. Customer satisfaction is an important factor in building long-term loyalty, while product quality, service quality, and price are the main variables that influence customer perception. This study uses a quantitative approach with a survey method. The study population was all customers of CV. Pabrik Baju Bandung, with a sample of 120 respondents selected using a purposive sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using multiple regression and mediation tests to determine direct and indirect relationships between variables. The results showed that product quality has a positive and significant effect on customer satisfaction, as does service quality. Price also has a positive effect on customer satisfaction, but with a lower effect than the quality variable. Customer satisfaction was proven to be a significant mediator between product quality, service quality, and price on customer loyalty. In other words, increasing product and service quality in line with a price that is considered reasonable can increase satisfaction, which in turn encourages customer loyalty. These findings emphasize the importance of a marketing strategy that emphasizes product quality, service quality, and competitive pricing to retain customers. This research provides practical implications for the management of CV. Pabrik Baju Bandung in formulating more effective marketing policies and increasing customer satisfaction and loyalty.